THE USE OF MOVIE CLIPS TO IMPROVE VOCABULARY MASTERY OF NINTH GRADE STUDENTS AT MTS MUHAMMADIYAH AL-HAQ PALU - Lakoro, Wahyu; Jamiluddin, Jamiluddin; Wahyudin, Wahyudin; Mukrim, Mukrim (Institut Pendidikan Tapanuli Selatan, 2025)
This research aims to examine the effect of using movie clips in improving vocabulary mastery of ninth grade students at MTs Muhammadiyah Al-Haq Palu. The study applied a quasi-experimental design with two groups, namely an experimental group and a control group. The sample consisted of 30 ninth-grade students selected through purposive sampling. The instruments used were matching-word and fill-in-the-blank tests. The findings revealed that the average score of the experimental class significantly increased from 63.83 to 96.16, while the control class increased from 58.83 to 79.83. The t-counted value was higher than the t-table value (1.703 > 1.693), indicating that the research hypothesis was accepted. Thus, the use of movie clips is effective in enhancing students’ vocabulary mastery.